Effects of prophylactic ankle and knee braces on leg stiffness during hopping - Hobara H; Hashizume S; Kobayashi Y (Dove Medical Press, 2017)
Hiroaki Hobara, Satoru Hashizume, Yoshiyuki Kobayashi Human Informatics Research Institute, National Institute of Advanced Industrial Science and Technology, Tokyo, Japan Abstract: During human movement, the leg can be represented as a mechanical spring, with its stiffness potentially contributing to sports performance and injury prevention. Although many individuals perform athletic activities with joint stabilizers, little is known about the effects of prophylactic lower extremity braces on leg stiffness. The objective of this study was to investigate the effect of ankle and/or knee braces on leg stiffness measured during one-legged hopping at a range of frequencies. Thirteen male participants performed one-legged hopping with their dominant leg at frequencies of 2.2, 2.6, and 3.0 Hz. All participants were randomly tested under the following four brace conditions: 1) no brace (control), 2) prophylactic ankle brace, 3) prophylactic knee brace, and 4) prophylactic ankle and knee braces. Based on a spring–mass model, leg stiffness was calculated using data from an accelerometer. It was found that leg stiffness increased with increasing hopping frequency for each brace condition. However, there were no significant differences in leg stiffness among the four brace conditions at the three hopping frequencies. Since some level of leg stiffness is needed for optimal athletic performance and training, these results suggest that ankle and knee braces do not significantly interfere with dynamic hopping activities. Keywords: spring–mass model, injury prevention, compensatory strategy